2009
DOI: 10.1111/j.1365-2672.2009.04355.x
|View full text |Cite
|
Sign up to set email alerts
|

Siderophores mediate reduced and increased uptake of cadmium byStreptomyces tendaeF4 and sunflower (Helianthus annuus), respectively

Abstract: Aims:  As a toxic metal, cadmium (Cd) affects microbial and plant metabolic processes, thereby potentially reducing the efficiency of microbe or plant‐mediated remediation of Cd‐polluted soil. The role of siderophores produced by Streptomyces tendae F4 in the uptake of Cd by bacteria and plant was investigated to gain insight into the influence of siderophores on Cd availability to micro‐organisms and plants. Methods and Results:  The bacterium was cultured under siderophore‐inducing conditions in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(139 citation statements)
references
References 59 publications
4
118
0
1
Order By: Relevance
“…4a and b). This result suggests that EG16 cells exposed to Cd have an increased requirement for Fe, which may help to counteract Cd toxicity (23).…”
Section: Mechanisms Of CD Accumulation In Eg16mentioning
confidence: 80%
See 1 more Smart Citation
“…4a and b). This result suggests that EG16 cells exposed to Cd have an increased requirement for Fe, which may help to counteract Cd toxicity (23).…”
Section: Mechanisms Of CD Accumulation In Eg16mentioning
confidence: 80%
“…Microbes have developed several metal resistance mechanisms in response to heavy metal stress, including intracellular and/or extracellular sequestration, efflux systems to export excess metal ions from bacterial cells, and the transformation of metals into a less toxic form by enzymatic detoxification (23)(24)(25)(26). It has been widely accepted that in the model bacterium Cupriavidus metallidurans, these mechanisms appear to be cooperative, not metal specific, and are controlled by a complex regulatory network involving several clusters of genes and functions (1,27).…”
mentioning
confidence: 99%
“…It was suggested that the synthesis of siderophores is associated with growth-promoting and antagonistic activity against phytopathogens [3]. In the soil, ability to produce siderophores plays a central role in the capacity of different bacteria to promote plant development due to increasing the iron absorption by plants and defense of plants from toxic metals such as nickel and cadmium [39] [40]. The antagonism against pathogenic bacteria and fungi is based on the iron binding by sidero-phore-producing bacteria that limits iron availability for other microorganisms and primarily for phytopathogenic micromycetes [41].…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with a previous report that EDDS was most effective in terms of solubilizing soil Cu for root uptake and translocation into aboveground biomass [17,19]. The high root concentration of metals (Cu or Zn) in the DGS6 + EDDS treatment group could be the result of: (1) the high biomass and the presence of dissolved metals in the soil solution, which would increase the root volume and allow roots to adsorb more metals; and (2) siderophores produced by the inoculant DGS6, which would solubilize metals and facilitate metal uptake by plant roots [29,36]. In the present study, the plant tissues were washed with only DIW before freeze drying instead of being soaked in solution (such as CaCl 2 ) to dissolve metals bound to the cell walls, which would contribute to the root uptake of metals.…”
Section: Effects Of Dgs6 and Edds On Trace Metal Uptakementioning
confidence: 99%